A novel voltage lifting technique of switched-inductor cell based modified LUO converter topology for water pumping system - Sweatha, Aseela; Baskaran, Balasubramanian; Duraipandy, P. (Institute of Advanced Engineering and Science, 2023)
The persistent exhaustion of traditional energy sources with their impacts on the environment has been initiating a significant interest in a selection of renewable-energy sources (RES) based water-pumping system. Among several renewable sources, solar-PV is the most promising and practical source for water-pumping applications that can be easily installed on a building's roof. The available solar-PV energy is integrated to AC electric motor through front-end DC-DC boost converter topology. Among the various DC-DC converter topologies, a novel switched-inductor type modified LUO converter has been proposed for solar-PV powered water pumping system. The proposed switched-inductor type modified LUO (SI-MLUO) converter have simple structure which delivers high voltage gain with low leakage currents, low current ripples, reduced voltage spikes, low dv/dt stress and high efficiency over the several conventional DC-DC converters. The operating modes and performance of proposed SI-MLUO converter topology is verified by using MATLAB/Simulink tool, simulation results are validated with conventional topologies.